“Happy Housewives”: Sisters in the Struggle for Women’s Rights - Wilson, Emily (Kansas State University. K-State Libraries, 2016)
““Happy Housewives”: Sisters in the Struggle for Women’s Rights” discusses social advancement from the perspective of an often unacknowledged group of people, the domestic and motherly “happy housewives”, who played a unique and unexpectedly important role in the progress of the Women’s Rights Movement in the 19th century. This paper argues that the women who prescribed to the ideology of separate spheres—that man had his place in society and woman had hers in the home—though often belittled, were essential to the progress of the Women’s Rights Movement. While outspoken suffragettes paraded the streets and outwardly protested for women’s rights, the “happy housewives” expanded women’s influence and societal distinction in subtle but significant ways that changed women’s role in the United States forever. Primary sources that support this claim include personal accounts and letters from “happy housewives”, sermons on the subject of women’s role in society, articles published in ladies’ magazines by and for the “happy housewives”, speeches, newspaper publications, cookbooks, and teachers’ guides.
Kirmser Undergraduate Research Award - Individual Non-Freshman, honorable mention
Citation: Wilson, E. (2016). “Happy Housewives”: Sisters in the Struggle for Women’s Rights. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Women’s Rights Movement